2017
DOI: 10.1111/jep.12663
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Ezetimibe to statins for patients at high cardiovascular risk: Systematic review of patient‐important outcomes

Abstract: Ezetimibe is widely used in combination with statins to reduce low-density lipoprotein. We sought to examine the impact of ezetimibe when added to statins on patient-important outcomes. Medline, EMBASE, CINAHL, and CENTRAL were searched through July, 2016. Randomized controlled trials (RCTs) of ezetimibe combined with statins versus statins alone that followed patients for at least 6 months and reported on at least one of all-cause mortality, cardiovascular deaths, non-fatal myocardial infarctions (MI), and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…26 The addition of ezetimibe to a moderate-dose statin is likely to result in 17 fewer myocardial infarctions and 6 fewer strokes per 1000 treated patients over 6 years. 27 In this study, the mean percent change in LDL-C level at 8 weeks was 450% for all doses of ezetimibe/rosuvastatin combination therapy. According to the 2016 ESC/EAS guideline for management of dyslipidemia, a reduction in LDL-C level of at least 50% is recommended in patients with more than high risk.…”
Section: Discussionmentioning
confidence: 57%
“…26 The addition of ezetimibe to a moderate-dose statin is likely to result in 17 fewer myocardial infarctions and 6 fewer strokes per 1000 treated patients over 6 years. 27 In this study, the mean percent change in LDL-C level at 8 weeks was 450% for all doses of ezetimibe/rosuvastatin combination therapy. According to the 2016 ESC/EAS guideline for management of dyslipidemia, a reduction in LDL-C level of at least 50% is recommended in patients with more than high risk.…”
Section: Discussionmentioning
confidence: 57%
“…Recent reviews and meta-analyses of RCTs, including the IMPROVE-IT study, showed that ezetimibe was likely associated with a reduction of the risk of myocardial infarction and stroke, without affecting the risk of overall or cardiovascular mortality or newly-developed cancer [ 21 22 ]. However, published reviews reported marginal cardiovascular benefits of ezetimibe when ezetimibe was added to statins for reducing nonfatal myocardial infarction and stroke (17 fewer myocardial infarctions and six fewer strokes per 1,000 persons treated over 6 years) [ 21 22 23 24 ]. This uncertainty is reflected in the absence of a consensus regarding ezetimibe in international guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have assessed the efficacy and safety of ezetimibe [15][16][17][18][19][20], this study is the first systematic literature review and meta-analysis of LDL-C lowering with ezetimibe in patients with ASCVD since the results of the IMPROVE-IT cardiovascular outcomes trial were published. In the present analysis, combination ezetimibe plus statin therapy resulted in a modest (relative to other treatment options) additional decrease in LDL-C compared with statin monotherapy (LDL-C mean difference − 21.86 mg/dL after 6 months of treatment), which was unaffected by treatment duration or a patient's prior history of statin therapy.…”
Section: Discussionmentioning
confidence: 99%